Mortality of cadmium-exposed workers. A five-year update. - Kazantzis, G.; Lam, T. H.; Sullivan, K. R. (Scandinavian Journal of Work, Environment & Health, 1988)
A cohort mortality study of cadmium-exposed workers initially followed to the end of 1979 has been updated for a further five years. The update has confirmed the findings of the original study with a significant excess risk from bronchitis related to intensity of exposure, although over the five-year period the excess mortality was no longer significant, a finding suggesting that the risk from bronchitis may now be declining in this cohort. In contrast, there is now a stronger indication of a excess risk from lung cancer related to intensity of exposure, significant for both the total and the five-year periods. There was again no increased risk from prostatic cancer, and from this and other studies it appears unlikely that cadmium, in the concentrations encountered in this and other recent studies, acts as a prostatic carcinogen. As in the initial study, there was no significant excess risk from hypertensive disease, nor any suggestion of an increased risk from cerebrovascular or renal disease.